2002
DOI: 10.1063/1.1509861
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal polymorph of tantalum–pentoxide with enhanced dielectric constant

Abstract: A tantalum–pentoxide dielectric with an enhanced permittivity of over 50 was found to be crystallized in a hexagonal symmetry with a=0.628 nm and c=0.389 nm. The incommensurate epitaxy of tantalum pentoxide on hcp-ruthenium metal stabilizes the hexagonal phase with √3-time periodicity in plane, as compared with that of the known hexagonal δ phase. The crystallographic assumption, which is based on one-dimensional Ta–O–Ta chain along the c axis, can explain large polarizability caused by delocalized electrons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 9 publications
2
31
0
Order By: Relevance
“…It is thought that this observation is strongly related to the metallic Ta present inside the films, since the presence of free electrons is known to increase the polarizability of a material. Elsewhere indeed, Hiratani et al have reported that delocalized electrons created by low oxygen occupancy along the c-axis increase the dielectric constant of Ta 2 O 5 grown on a Ru substrate [12]. The situation is similar here, with the tetragonal phase in these ZrO 2 / Ta 2 O 5 films stabilized by Ta doping mainly along the (101) direction, and the formation of metallic Ta supplying free electrons.…”
Section: Resultssupporting
confidence: 59%
“…It is thought that this observation is strongly related to the metallic Ta present inside the films, since the presence of free electrons is known to increase the polarizability of a material. Elsewhere indeed, Hiratani et al have reported that delocalized electrons created by low oxygen occupancy along the c-axis increase the dielectric constant of Ta 2 O 5 grown on a Ru substrate [12]. The situation is similar here, with the tetragonal phase in these ZrO 2 / Ta 2 O 5 films stabilized by Ta doping mainly along the (101) direction, and the formation of metallic Ta supplying free electrons.…”
Section: Resultssupporting
confidence: 59%
“…Figure 6 shows a nano-area diffraction pattern when the electron beam was focused on a single grain and aligned normal to the film surface. The diffraction pattem shows six-fold symmetry of the Nb205, similar to the incommensurate heteroepitaxy of a Ta20S film on a hexagonal Ru electrode (2). As in our results from a cross-sectional view and XRD, the crystal structure was determined to be a hexagonal variant with a = 0.63 nm and c = 0.39 nm.…”
mentioning
confidence: 86%
“…We have previously shown that MIM-Ta205 on a Ru electrode is crystallized in a hexagonal structure because of an incommensurate epitaxy and that it bas a permittivity higher than SO (2). On the other hand, it bas been reported that pseudo-hexagonal Nb205 may exist at a low temperature, i.e., 600°C (3)(4)(5).…”
Section: Introductionmentioning
confidence: 97%
“…These results indicate that the crystallization temperature of Ta 2 O 5 thin films needs to be as high as 700 • C, which is similar to that reported in literature. 16 …”
Section: Crystallization Of Ta 2 O 5 Thin Films Annealed Under Atmospmentioning
confidence: 97%